Regional migration governance: contributions to a sustainable international migration architecture - Dick, Eva; Schraven, Benjamin; Koch, Anne; Etzold, Benjamin (2018)
Abstract: Technical and financial capacities of regional organizations ought to be improved so that they can tackle regional migratory challenges effectively and in line with global regulatory requirements. This is not only true for security-relevant areas such as the protection of borders or migration control but also for the implementation of regional standards pertaining to the freedom of movement and, in particular, for the protection of refugees and vulnerable migrants. It also applies to promoting the positive effect migration has on human development. Regional and inter-regional dialogue forums help to mediate conflicts between different national interests and can strengthen the overall coherence of international migration policy. Building up these forums ought to be promoted, the exchange between national, regional and global actors intensified, and the inclusion of civil society actors in regional cooperation formats improved. Regional organizations have developed groundbreaking nor